DEVELOPING A MODEL OF HISTORY LEARNING MANAGEMENT BASED ON CONTEXTUAL APPROACH TO IMPROVE HISTORY AWARENESS - Soelistijanto, R.; Rahman, Maman; Raharjo, Tri joko (The Journal of Educational Development, 2017)
The current model of history teaching and learning is still oriented toward delivering learning materials so history awareness among the learners is not optimally achieved. This study is intended to analyze the implementation of the current management of history teaching and learning, to develop a model of history learning management based on the contextual approach to improve history awareness, and to test the feasibility of the model. This study adopted a research and development design. The data were collected by using observation, interviews, questionnaires and documents, and analysed by using a descriptive and analytical qualitative analysis. The results show that the teaching of history is currently teacher-centered, by using a lecture method, with very limited teaching media and references. Developing a management model of contextual history learning is a way to improve history awareness. The model was validated by experts by the average scale of 3.81 and by practitioners by the average scale of 4.00. The final model consists of planning, observation, development and application. The model can improve the history awareness of the VHS learners better if compared to the conventional model (ttest = 5.316 at p < 0.05).